2018
DOI: 10.1002/ecs2.2492
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of fire regimes in adjacent Native American and public forests, New Mexico, USA

Abstract: Statistical descriptions of reconstructed fire regimes are often extrapolated from a composite of small forest stands to represent extensive geographical areas. However, statistical properties of fire regimes are scale‐dependent, thus causing some extrapolations from fine scale to coarse scale and comparisons between fire‐scar‐based reconstructions to be inappropriate. We assessed landscape fire regimes of the Sacramento Mountains, in southern New Mexico, using dendrochronological methods and a variety of fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…(1998) described mixed‐conifer forests in the Sacramento Mountains as being dominated by ponderosa pine and Azpeleta Tarancón et al. (2018) found a higher amount of ponderosa pine remnants than any other coniferous tree within many sites in the MATL. Forest treatments in the MATL such as fire exclusion in the early 1900s (Azpeleta Tarancón et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1998) described mixed‐conifer forests in the Sacramento Mountains as being dominated by ponderosa pine and Azpeleta Tarancón et al. (2018) found a higher amount of ponderosa pine remnants than any other coniferous tree within many sites in the MATL. Forest treatments in the MATL such as fire exclusion in the early 1900s (Azpeleta Tarancón et al.…”
Section: Discussionmentioning
confidence: 99%
“…Forest treatments in the MATL such as fire exclusion in the early 1900s (Azpeleta Tarancón et al. 2018), the selective logging of LT conducted by the Mescalero Forest Products sawmill with a preference for ponderosa pine, and the bark beetle and dwarf mistletoe outbreaks on commercial stands followed by salvage and sanitation cuttings (HRA 1981, Hoyt et al. 2017), are the most probable drivers of this change, affecting negatively ponderosa pine trees with the unintended effect of favoring Douglas fir tree encroachment in the gaps historically dominated by ponderosa pine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling was selective in an area of about 20 ha (Figure 1) including remote areas, where forest roads and trails are used for access. Sampling was designed in this way to collect the greatest number of fire occurrence dates on trees with evidence of fire damage (Azpeleta Tarancón, Fulé, Sánchez Meador, Kim, & Padilla, 2018;Meunier & Shea, 2020). Part sections of dead (standing or felled) and live trees with well-preserved scars and as long-lived as possible were removed using a chainsaw (Sthil MS 361) (Yocom Kent, 2014).…”
Section: Field Methodsmentioning
confidence: 99%
“…Using a geographical interpolation and model combined with fire scars to modernize the historical fire areas is meaningful for spatially explicit fire frequency reconstruction [18,19]. Azpeleta Tarancón, et al [20] used dendrochronological methods and various fire statistics to reconstruct and assess landscape fire regimes. Their results showed that historical fires were synchronous with drought years and were often preceded by wet years.…”
Section: Introductionmentioning
confidence: 99%